Optical properties and electronic structure of V2O5, V2O3 and VO2 - Schneider, Krystyna (Journal of materials science. Materials in electronics, 2020)
The electronic structure of the three main vanadium oxides—V 2 O 3 , VO 2 and V 2 O 5 —is reviewed. The optical properties of vanadium pentoxide thin films were determined. It was found that a direct allowed transition is the most probable one in the studied vanadium pentoxide thin films.